pengaruh penyuluhan tentang penyakit menular seksual (PMS) terhadap pengetahuan remaja tentang penyakit menukar seksual (PMS) di SMK Muhammadiyah 2 - Zainuri, Imam; Rahayu, Sri (JURNAL KEPERAWATAN BINA SEHAT, 2011)
A sexually transmitted disease(STDs) isdiseasesthat ariseorbe transmittedbysexualrelationswiththe onset ofclinical manifestationsofabnormalities, especially in the genitals. A purposes of research is to know the effect of knowledge of teenagers about sexually transmitted diseases (STDs) before and after given counseling about sexually transmitted diseases (STDs) in SMK Muhammadiyah 2 Kutorejo Mojokerto. Research designusedin this research isa comparativeanalyticalapproachwithonegrouppretest-posttestdesign. The population is all students SMK Muhammadiyah Kutorejo Mojokerto totaling 240 students in this research, researchers used a way of sampling is probability sampling with a random sampling, with the number of sampling as many (20%) 48 students.The independent variableiseducationaboutsexuallytransmitteddiseases(STDs),the dependent variableis theknowledgeteenagersaboutsexuallytransmitteddiseases(STDs) beforeand aftergivencounseling aboutsexuallytransmitteddiseases(STDs). Dataobtained bydistributing questionnairesandcounseling. The results in the Wilcoxon statistical can be of value Z = -4264, where â„“ = 0.000 and â„“ value <.05 so H0is rejected and H1is accepted which means there is the influence of counseling about sexually transmitted diseases (STDs) to the knowledge of students SMK Muhammadiyah 2 Kutorejo Mojokerto, and can apply the results of counseling about sexually transmitted diseases (STDs).Keywords: Knowledge, sexually transmitted diseases(STDs), ofteenagers SMKMuhammadiyah2